Peran Teacher Librarian dalam Meningkatkan Minat Baca Siswa di YP Raudhatul Faizin Desa Tanjung Rejo - Siagian, Asyah; Siregar, Yusra Dewi (Lembaga Yasin AlSys, 2024)
This study aims to find out how the role of the teacher librariansnncreasing students’nteresetn YP Raudhatul Faizin village Tanjung Rejo and factors and constraintsn the role of teacher librariansnncreasing thentereset of students at YP Raudhatul Faizin Village Tanjung Rejo. The type of research useds a qualitative approach. The techniques used for data collection are observation,nterviews and documentation. While the data analysis technique useds data reduction, presentation of data and conclusiion drawings. The results showed that the role carried out by the teachernncreasing thenterest of students was to dominate to the role ofnformation providers, motivators, facilitators, showtles and supervisors. Librarians have carried out their roles wellnncreasing thenterest of reading students by becoming an educator, manager and administrator. Factor and obstacles the role of the teacher librariannncreasing thenterest of students at YP Raudhatul Faizin Village Tanjung Rejos a lack of funds and facilitiesnadequate to manage and add library facilities such as bookshelves, tablles, chairs and so on.